The Influence Of Training And School Principal Leadership On Teachers And Administrative Staff Performance At Smpn 1 South Bengkulu (A Case Study At Smpn 1 South Bengkulu) - Wahyuningtias, Anggea; Irwanto, Tito; Rydarto, Dennis (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of training and school principal leadership on the performance of teachers and administrative staff at SMPN 1 South Bengkulu. The sample used in this study is 50 teachers and administrative staff at SMPN 1 South Bengkulu. Data collection was done using questionnaires and the analysis methods used were validity test, reliability test, classic assumption test, and hypothesis test. The research results indicate that the regression value Y = 6.868 + 0.371 (X1) + 0.322 (X2) with a positive regression direction, indicating that training significantly affects the performance of teachers and administrative staff, as the significant value is 0.000 less than 0.05. This means that training will improve the performance of teachers and administrative staff at SMPN 1 South Bengkulu. School principal leadership significantly affects the performance of teachers and administrative staff at SMPN 1 South Bengkulu, as the significant value of 0.000 is less than 0.05. This means that school principal leadership will enhance the performance of teachers and administrative staff at SMPN 1 South Bengkulu. Training and school principal leadership significantly influence the performance of teachers and administrative staff, thus proving the initial hypothesis (Ha accepted). This implies that there is a significant impact of training and school principal leadership on the performance of teachers and administrative staff jointly. The coefficient of determination R square is 0.340. This means that training and school principal leadership influence the performance of teachers and administrative staff by 80%, while the remaining (100-80% = 20%) is influenced by other factors not examined in this study.